2019
DOI: 10.21608/ejnf.2019.79474
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Nutrients Digestibility and Carcass Measurements of Growing Rabbits Fed Diets Incorporated With Lentil or Chickpea Screening by-Products.

Abstract: his work aimed to study the influence of replacement 15 or 30% of soybean meal protein by either lentil screening by-products protein (LSBP) or chickpea screening by-products protein (CSBP) on performance, nutrients digestibility, plasma parameters, carcass measurements and economic profitability of growing rabbits. Sixty New Zealand White (NZW) growing rabbits, six weeks of age, were divided to five experimental groups. Each group included four replicates (three rabbits each) as follow: control group fed basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
4
0
1
Order By: Relevance
“…Whereas, liver%, kidneys% and edible giblets % were not statistically affected by the inclusion of LSB in rabbit's diets. The results are inconsistent with previous studies (Suliman et al, 2019) who suggested that the inclusion of lentil screening by-product protein at a level of 15% significantly decreased (P<0.05) total edible parts % compared with the control group. Moreover, Ayaşan et al, (2018) found that the use of lentil by-products in quail's diets at levels of 5, 10, 15 and 20% reduced the dressing percentage than in the control group, even though the reduction was significant in 5 and 10% of lentil by-products fed groups.…”
Section: Carcass Characteristicscontrasting
confidence: 99%
See 4 more Smart Citations
“…Whereas, liver%, kidneys% and edible giblets % were not statistically affected by the inclusion of LSB in rabbit's diets. The results are inconsistent with previous studies (Suliman et al, 2019) who suggested that the inclusion of lentil screening by-product protein at a level of 15% significantly decreased (P<0.05) total edible parts % compared with the control group. Moreover, Ayaşan et al, (2018) found that the use of lentil by-products in quail's diets at levels of 5, 10, 15 and 20% reduced the dressing percentage than in the control group, even though the reduction was significant in 5 and 10% of lentil by-products fed groups.…”
Section: Carcass Characteristicscontrasting
confidence: 99%
“…While, TDN and DE values were higher (P<0.05) with rabbits group fed 5% LSB than those fed 15% LSB. This finding agreed with those reported by Suliman et al, (2019) who stated that no significant changes were noticed in all nutrients digestibility of DM, OM, CP, CF, EE and NFE between groups of rabbits fed 15 and 30%LSBP. This study reveals that the enhanced digestibility in the groups fed diets contained different levels of LSB can be attributed to protein structures and energy content of LSB as it was mentioned in Table (2) that lentil screening by-product have a relatively high protein (26.60%) and gross energy content (4400 kcal/kg) and low digestive inhibitors.…”
Section: Digestibility Of Nutrientssupporting
confidence: 93%
See 3 more Smart Citations